"No time for a solicitor": implications for delays on the take-up of legal advice - Kemp, Vicky (Sweet and Maxwell, 2013)
A study of police custody records highlighted variations between police stations both in the take-up of legal advice and also in the average length of time people were held in custody. To further explore unobserved factors which might impact on such variations a qualitative study has been undertaken of four large police stations. While there were found to be factors in common between police stations which related to delays, there were other factors which were specific to one or two stations only. There were also found to be implications for delays creating potential barriers to legal advice. Such factors raise questions about the extent to which PACE continues to provide sufficient legal safeguards for those held in police custody.